Design and construction of equipment for the elimination of saponin in Quinoa (Chenopodium quinoa Willd): Performance tests with Amarillo Marangani variety - Montañez Artica , Wilson Manuel (2024)
Quinoa is a very important grain for human nutrition; In recent years, several research studies have addressed its nutritional use; However, one of its main weaknesses is its saponin content, which is an anti-nutrient and has a bitter taste. The debittering process involves the principle of recirculation of large quantities of water, with the purpose of reducing the consumption of this substance, it is important to develop methodologies and equipment that improve the efficiency of these traditional washing methods and reduce the work of operators and processors with the intention of making it less costly. The objective of the present research work was to design and build a quinoa de- saponifier , Amarillo Maranganí variety, to evaluate the effect of washing time (5, 10 and 15 min) and the flow of water recirculated by pumping (15, 30 and 45 L/min), on the elimination of saponin to acceptable commercial levels. The results indicated that the highest saponin extraction was achieved when using washing times of 5 min with water flow rates of 15 L/min, and 51.75 % of the initial saponin content was eliminated. In general, it is stated that increasing the flow rate of the washing water reduces the extraction efficiency, but performing a second washing significantly reduces the extraction, the equipment developed presents promising characteristics for application in the industry.